Complementary Therapies 2022
DOI: 10.5772/intechopen.101619
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of Yoga in Stress, Anxiety and Depression

Abstract: Yoga is not only an art but also an ancient science that evolved more than 5000 years ago. It is practised by people from all walks of life in almost every part of the world. In the past, the practice, which was seen to be spiritual and divine, used to be confined to smaller groups of individuals who were seeking moksha or liberation; however, the trend has transformed over the decades. Today, there are so many yoga studios worldwide, and this has made it easy for yoga enthusiasts. This chapter investigates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…The exploration, however, requires further scrutiny to be conducted in order to determine the success of yoga in adults. 16 The above research studies have shown a positive influence of yoga therapy and yoga intervention on obesity and its related parameters. The present study is designed to use various yoga practices such as shatkarma (cleansing techniques), surya namaskar (sun salutation), pranayama (controlled breathing), and yoga nidra (for relaxation).…”
Section: Introductionmentioning
confidence: 94%
“…The exploration, however, requires further scrutiny to be conducted in order to determine the success of yoga in adults. 16 The above research studies have shown a positive influence of yoga therapy and yoga intervention on obesity and its related parameters. The present study is designed to use various yoga practices such as shatkarma (cleansing techniques), surya namaskar (sun salutation), pranayama (controlled breathing), and yoga nidra (for relaxation).…”
Section: Introductionmentioning
confidence: 94%